Chapter Professionalisation of Adult Education in Slovenia from a Multi-level Perspective - Kovšca, Mateja (Studies on Adult Learning and Education, 2023)
The adult education (AE) research community emphasise the importance of well-qualified personnel working in the field of AE. However, the field is facing with challenges achieving this aim. This chapter research professionalisation of AE from a multi-level perspective in one European Union member state - Slovenia. Based on empirical data from Slovenia, the chapter argues that coordination at three levels is important: at the national level, professionalisation is strengthened by state policies and regulations; at the organisational level, the professional development of adult educators is supported by organisations; and at the individual level, the focus is on professional knowledge and strengthening the professional identity of adult educators.